1992
DOI: 10.1111/j.1600-0609.1992.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of thrombocytopenia in patients with lymphoproliferative diseases

Abstract: Different factors are involved in the development of thrombocytopenia in patients with lymphoproliferative disorders. Significant correlation was detected between the number of megakaryocytes in bone marrow and platelet count (r = 0.485, p = 0.002, n = 37) and significant difference between the number of megakaryocyte in patients with normal platelet count (>200000/μl) and patients with marked thrombocytopenia (platelet count < 100000/μl). All patients in the latter group (n = 15) had a relatively low number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A previous study reported that platelet antibody IgG (PA-IgG) levels were elevated in 46% of patients with lymphoproliferative disorders (25). There was a certain correlation between thrombocytopenia and the increase of PA-IgG levels in patients with ITP after resection (26).…”
Section: Discussionmentioning
confidence: 94%
“…A previous study reported that platelet antibody IgG (PA-IgG) levels were elevated in 46% of patients with lymphoproliferative disorders (25). There was a certain correlation between thrombocytopenia and the increase of PA-IgG levels in patients with ITP after resection (26).…”
Section: Discussionmentioning
confidence: 94%
“…PA-IgG were measured in washed platelets (see above) as previously described [18]. PA-IgG were detected by binding of 125 I-labeled affinity purified goat antihuman IgG antibodies (IMTEK, Moscow, Russian Federation).…”
Section: Methodsmentioning
confidence: 99%
“…Immune thrombocytopenia is often seen in patients with B‐cell lymphoproliferative disorders 20‐22 . Rather than specific autoantibody being produced by the monoclonal malignant population itself, it is more likely that the inherent immunomodulated state in these diseases allows the emergence of autoreactive clones 23 .…”
mentioning
confidence: 99%